Kajian Hukum dan Lingkungan Pengembangan Konsep Penataan Ruang Kampung Kinamang Kelurahan Malalayang 2 Kota Manado : The Legal and Environmental Studies for the Development of the Spatial Planning Concept of Kinamang Village, Malalayang 2 Village, Manado City (Tumou Tou: Jurnal Pengabdian Masyarakat, 2023)
Kampung Kinamang is one of the coastal villages inhabited by maritime communities who generally work as fishermen. This village is located in a coastal area near the coast with a relatively low altitude so it is prone to damage by big wave action. The residents in this village face many problems, especially related to safety, the threat of eviction (agrarian conflict) and also the potential for health problems and poor aesthetics due to poor waste management. These three main problems have been agreed upon at an early stage to find a solution together with the PKM implementers with the title "development of the spatial planning concept of the kinamang village". This PKM will use several approaches in solving problems faced by partners, and it is hoped that the results will be useful for partner residents in improving their quality of life.